Socio-demographic and clinical features of Irish iatrogenic hepatitis C patients: a cross-sectional survey - Cunningham Caitriona; McKenna Olivia; Blake Catherine (BMC, 2009)
Abstract Background A discrete sub-group of iatrogenically-acquired hepatitis C virus (HCV)-infected individuals exists in the Irish population on whom limited current research data is available. The aim of this study was to establish a current profile of the socio-demographic and clinical characteristics of the Irish iatrogenic hepatitis C population and to determine factors predicting symptoms experienced. Methods An anonymous, national, cross-sectional survey was conducted to explore this populations' self-reported health and social attributes. Data were collected on 290 respondents. Results Mean time since infection was 26 years. Eighty-four percent (n = 237) of respondents were female (mean age = 55.9 ± 9.6 years). Hepatic and extra-hepatic symptoms were common (62% and 99% respectively). Fatigue and pain were frequent complaints while 89% reported diagnosed co-morbid disease. On logistic regression, female gender, age and co-morbid disease emerged as independent predictors of self-reported symptoms. Conclusion This study describes the current status of the iatrogenically infected patient cohort in Ireland, adding to existing knowledge regarding the clinical course and consequences of HCV infection. Changing healthcare needs were shown by comparison with earlier surveys in this same population, in terms of disease progression, development of co-morbid disease and ageing.